Wooden temple in the Russian North cultural landscape - Permilovskaya, Anna (project baikal, 2025)
Kimzha village in the Mezen district is a unique historical settlement in Russia. Here, the traditional layout and wooden architecture of the 18th-20th centuries have been preserved, including the Church of the Hodegetria (1709), peasant houses, barns, baths, windmills, votive and cemetery crosses, as well as folk culture, folklore, traditional system of nature management, style of life and cultural landscape. The architectural and sacred dominant of the settlement is the Church of the Hodegetria, one of the three wooden churches of the rare ‘tent on a cross-like barrel’ type that have survived in the Russian North. The article presents the author’s expeditionary and archival research, including new materials based on the results of the expedition of 2024.
Keywords: wooden architecture; cultural landscape; temple; Russian North; Orthodoxy